VARIASI KOMPOSISI DAN MAKNA KATA MAJEMUK (FUKUGOUGO) DALAM BUKU KUMPULAN ESAI HITORI ZUMOU KARYA SAKURA MOMOKO - Eka Jayanti, Ni Wayan (Humanis; Volume 11. No 1. April 2015, 2015)
This research analyzed the composition variation and meaning of compound word in Japanese Languange. The data source was taken from an essay compilation book by Sakura Momoko entitled “Hitori Zumou”. The method of this research was descriptive method. The theories used for this research was proposed by Shibatani and Chaer. The analysis results show that there are 18 composition variations of compound words that can be formed. The 18 variations divided into three categories: Native Compounds, Sino-Japanese Compounds, and Hybrid Compounds. The meaning formed by these compound words also can be divided into three categories: the meaning produced by both of the forming words, the meaning produced by one of the forming words, and the meaning that was not produced by the forming words.
Keywords: compound word, composition variation, meaning